Comparison of E-Commerce Transactions in Conventional Accounting and Sharia Accounting - Sudarmanto, Eko (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
Muamalah and business develop along withtechnological developments and human needs. When thebusiness model and muamalah develop, this developmentmust be responded to appropriately and carefully. Not onlyrelated to the aspects of benefits, harm and legalconditions that govern it, but also must be prepared anddeveloped the model and accounting system needed. Oneform of the new trading business is e-commerce. Namelybusiness activities involving consumers, manufacturers,providers, and brokers using computer networks, namelythe internet. So that e-commerce transactions have severalcharacteristics, including: unlimited transactions,anonym transactions, digital and non-digital products,and intangible goods. Based on several characteristicsfound in e-commerce transactions, the applicable lawrelated to the transaction is the law regarding longdistance buying, salam and salaf law, hawalah law andelectronic money. With the different viewpoints and legalbasis for e-commerce transactions, the accountingtreatment between conventional and Sharia systems alsohas several differences. Sharia Accounting Bai’ as-Salamis a buying and selling accounting system that is mostsuitable for e-commerce transactions